Analisis Metafora Visual Pada Iklan Televisi Go-Jek versi Cerdikiawan - Winata Faturahman (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Advertising is a means to promote a product or service by a producer so that the product or service is known to the public. The development of advertisements began with print advertisements which are now found in various audio visual forms. Audio visual advertising is an ad that combines moving images and sound as a support for the delivery of information. Compared to print advertisements, audio visual advertisements are more attractive because of their dynamic nature so that the communication process in them will be quickly conveyed. Go-jek is a business that is engaged in services that are well known to the public. Because of its wide reach, Go-jek always innovates for the satisfaction of its customers. The innovation is not only done through the services provided, but also in terms of promotion. Go-jek promotion is carried out by spreading information about its services through print and audio visual advertisements. One of the Go-jek audio visual ads on television is the clever version of Go-jek. According to his understanding, metaphor means equality or comparison. In the Cleverly Go-Jek ad version, there is a visual metaphor to communicate to the public about the services provided with an attractive visual.